2020
DOI: 10.1515/cdbme-2020-3028
|View full text |Cite
|
Sign up to set email alerts
|

Reduced order method for finite difference modeling of cardiac propagation

Abstract: Efficient numerical simulation of cardiac electrophysiology is crucial for studying the electrical properties of the heart tissue. The cardiac bidomain model is the most widely accepted representation of the electrical behaviour of the heart muscle. The bidomain model offers fast cardiac potential variation, which can lead to high computational cost due to the required large grid sizes and small time steps. In this paper, the complexity of the finite difference approximation of the bidomain equations is reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The performance of the method reported herein is in accordance with previous studies reporting a reduction of CPU time, from approximately 3 h for FEA to <1 s for reduced models (i.e., a 10 4 -fold reduction) ( Lu et al, 2018 ) and 5 min for FEA to 10 –5 s for reduced models (i.e., a 10 7 -fold reduction) ( Badrou et al, 2023 ). In comparison, a proper orthogonal decomposition (POD) was used by Ng et al for modelling the cardiac propagation and reported similar accuracy with a 10-fold reduction of computing time ( Khan et al, 2020 ). This difference of computing times might be explained by the difference of problems to learn.…”
Section: Discussionmentioning
confidence: 95%
“…The performance of the method reported herein is in accordance with previous studies reporting a reduction of CPU time, from approximately 3 h for FEA to <1 s for reduced models (i.e., a 10 4 -fold reduction) ( Lu et al, 2018 ) and 5 min for FEA to 10 –5 s for reduced models (i.e., a 10 7 -fold reduction) ( Badrou et al, 2023 ). In comparison, a proper orthogonal decomposition (POD) was used by Ng et al for modelling the cardiac propagation and reported similar accuracy with a 10-fold reduction of computing time ( Khan et al, 2020 ). This difference of computing times might be explained by the difference of problems to learn.…”
Section: Discussionmentioning
confidence: 95%